Potential Nanospray Inhalation of Remdesivir and Hydroxychloroquine using Poly (lactic-co-glycolic) Acid as Fast Delivery for Covid-19 Treatment. - Muhammad Taher; Siti Syazwani Shaari; Deny Susanti (IIUM Press, International Islamic University Malaysia, 2021)
Introduction: The oral medication of remdesivir and hydroxychloroquine face several limitations in covid-19 therapy.  Despite having the first-pass metabolism, it also has a limitation in the patient who has hospitalised with a severe covid-19 infection. It is especially for a drug that is targeting the angiotensin-converting enzyme II (ACE2) receptor where the receptors are found abundantly in the lung, kidney, heart, and gastrointestinal tract. Therefore, an alternative delivery such as nanospray inhalation would provide a great benefit to those patients. Methods: Scientific sources from Scopus, PubMed, Google Scholar, EBSCO, ScienceDirect, and Elsevier were accessed for publication of this review article regarding the nanospray inhalation for Covid-19. Results: Since the main organ infected by SARS-CoV-2 is the trachea and lung, inhalation may be the best route to deliver the drug to the site of action. It is proposed that poly (lactic-co-glycolic) acid to be used in the formulation. Conclusion: Poly (lactic-co-glycolic) acid (PLGA) is considered a suitable polymer since it is biocompatible and noncytotoxic, it is the most widely applied in drug delivery either as carrier or excipient for the optimal formulation and distribution of the drugs. Dry powder inhalation of remdesivir and hydroxychloroquine may be an alternative way to deliver the drug against Covid-19.